Effects of thrombopoietin on growth of hepatocellular carcinoma: Is thrombopoietin therapy for liver disease safe or not?. Issue 6 (16th November 2012) - Nozaki, Reiji; Murata, Soichiro; Nowatari, Takeshi; Maruyama, Takehito; Ikeda, Naoya; Kawasaki, Takuya; Fukunaga, Kiyoshi; Ohkohchi, Nobuhiro
<x xml:space="preserve">Abstract</x> Aim Liver cirrhosis (LC) is the end stage of chronic liver disease. No definitive pharmacological treatment is currently available. We previously reported that thrombopoietin (TPO) promoted liver regeneration and improved liver cirrhosis by increasing platelet count. TPO is therefore considered to be a therapeutic agent for LC; however, it is unclear whether TPO has proliferative effects on hepatocellular carcinoma (HCC), which arises frequently in cirrhotic livers. In this study, we examined the effects of TPO on growth of HCC. Methods Expression of the TPO receptor, myeloproliferative leukemia virus oncogene (MPL) was examined in various liver tumor cell lines and liver cell types. In an in vitro study, the effects of TPO on signal transduction, cell proliferation, migration and invasion were examined in Huh7 cells, in which MPL is highly expressed. In an in vivo study, we subcutaneously transplanted Huh7 cells into nude mice that were divided into a TPO‐treated group and a control group, and the tumor volume of each group was measured. Results MPL was expressed strongly in hepatocytes but not in other cell types. Among liver tumor cell lines, Huh7 showed the highest expression of MPL. In Huh7, the addition of TPO activated Akt phosphorylation but not cell proliferation, migration or invasion. In the mouse experiment, there was no significant difference in tumor volume between the two groups. Conclusion TPO had no proliferative effect on HCC in vitro or in vivo, and could therefore be useful in the treatment of liver cirrhosis.